Role of Natural Killer T Cells in the Development of Obesity and Insulin Resistance: Insights From Recent Progress - Satoh, Masashi; Iwabuchi, Kazuya (Frontiers in Immunology, 2018)
Natural killer T (NKTs) cells play important roles in adipose tissue inflammation, and thus influence the development of diet-induced obesity and insulin resistance. The interactions between cluster of differentiation (CD)1d and NKT T cell receptor are thought to be critical in this process, as demonstrated in two NKT cell-deficient mouse models—systemic CD1d gene knockout (KO) and prototypic Jα18 KO mice. The latter lacks some repertoires besides invariant (i)NKT cells due to manipulation of the Jα18 gene segment; therefore, the role of iNKT vs. variant NKT cells must be reinterpreted considering the availability of new Jα18 KO mice. NKT cells have varied roles in the development of obesity; indeed, studies have reported contradictory results depending on the mouse model, diet, and rearing conditions, all of which could affect the microbiome. In this mini-review, we discuss these points considering recent findings from our laboratory and others as well as the role of NKT cells in the development of obesity and insulin resistance based on data obtained from studies on conditional CD1d1 KO and new Jα18 KO mice generated through gene editing.